Implementasi Senam Prenatal Yoga Untuk Mengurangi Ketidaknyamanan Ibu Saat Hamil di Tangerang - Lastri Mei Winarni; Nuryanti (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this community service is to teach pregnant women about Prenatal Yoga Exercises to reduce the discomfort of pregnant women at RW 07 Margasari Karawaci Tangerang. The methods used in this community service are demonstrations and question and answer lectures. Measuring the discomfort of pregnant women using a questionnaire. The result was that 83.3% of mothers stated that they were satisfied with following prenatal yoga and 67.7% of mothers stated that their discomfort was reduced. The conclusion is that prenatal yoga can be an alternative for mother's activities in reducing discomfort during pregnancy.